Air transport growth and its impact on the environment in EU countries and Lithuania - Stankunas, J.; Vaitonyte, K. (Proceedings of National Aviation University (archive), 2003)
Tendencies in European Union and candidate counties transport system development, its impact on the environment, volume and kinds of losses caused by transport, tendencies in the Lithuanian air transport development are considered in this article